Oxytocin in the nucleus accumbens shell reverses CRFR2-evoked passive stress-coping after partner loss in monogamous male prairie voles - Bosch, Oliver J; Dabrowska, Joanna; Modi, Meera E.; Johnson, Zachary V.; Keebaugh, Alaine C.; Barrett, Catherine E.; Ahern, Todd H.; Guo, JiDong; Grinevich, Valéry; Rainnie, Donald G.; Neumann, Inga D.; Young, Larry J. (Psychoneuroendocrinology, 2016)
Loss of a partner can have severe effects on mental health. Here we explore the neural mechanisms underlying increased passive stress-coping, indicative of depressive-like behavior, following the loss of the female partner in the monogamous male prairie vole. We demonstrate that corticotropin-releasing factor receptor 2 (CRFR2) in the nucleus accumbens shell mediates social loss-induced passive coping. Further, we show that partner loss compromises the oxytocin system through multiple mechanisms. Finally, we provide evidence for an interaction of the CRFR2 and oxytocin systems in mediating the emotional consequences of partner loss. Our results suggest that chronic activation of CRFR2 and suppression of striatal oxytocin signaling following partner loss result in an aversive emotional state that may share underlying mechanisms with bereavement. We propose that the suppression of oxytocin signaling is likely adaptive during short separations to encourage reunion with the partner and may have evolved to maintain long-term partnerships. Additionally, therapeutic strategies targeting these systems should be considered for treatment of social loss-mediated depression.
Available online 23 November 2015
Gesehen am 18.05.2020